Kecemasan Dan Depresi Pada Penderita Diabetes Mellitus Tipe 2 Yang Mengalami Disfungsi Seksual Di Puskesmas Sibela Kota Surakarta - Insiyah Insiyah; Rini Tri Hastuti (Poltekkes Kemenkes Surakarta, 2018)
Background: The various symptoms will be experienced by patients with diabetes mellitus type 2 following they suffer from the disease. The symptoms include symptoms of anxiety and depression. During suffering from diabetes mellitus type 2, the patients also experienced the complication of the disease that effects the quality of life. Good management of the disease is very important to decrease mortality and morbidity. WHO stated that there is an increase of prevalence of diabetes mellitus type 2 in developing countries including Indonesia. This research aims to know the relationship between anxiety and depression to sexual dysfunction among woman with diabetes mellitus type 2 in Sibela Public Health Centre in Surakarta City. This research was also conducted to describe the level of anxiety, depression and sexual dysfunction among women with diabetes mellitus. Method: this research is non-eksperimen with a descriptive correlational design that describes research based on the distribution and then finds a correlation between one variable and other variables. Chi-Square SPSS (Statistical Program For Social Science) version 18 was utilized to analyze the data. Result: showed that there a correlation between anxiety and sexual dysfunction among women with diabetes mellitus with p-value = 0,002 ( p< 0,05). Conclusion: There was also correlation between depression and sexual dysfunction among women with diabetes mellitus with p-value = 0.000 (p < 0,05). Identification of the symptoms of anxiety, depression, sexual dysfunction is important in order to plan appropriate intervention to deal with the problem.